Effect of organic manures and silicon nutrition on the productivity and profitability of rice - Raajkiran, C; Jawahar, S; Kalaiyarasan, C; Suseendran, K; Elayaraja, D; Kandasamy, S; Swetha, E; Sheik, Shalik S; Senthilkumar, D; Vasanth, P (Plant Science Today, 2025)
Field experiments were conducted in 2022 and 2023 during the Kharif season at experimental farm, Department of Agronomy, Annamalai University, Tamil Nadu, India to study the effect of organic manures and silicon nutrition on the productivity and profitability of rice. The treatments included both organic manures (farmyard manure (FYM), green manure (GM), poultry manure (PM)) and recommended doses of fertilizers (RDF)). Silicon through Diatomaceous earth (DE) was tested in combination with the above nutrient sources. The treatments were arranged in randomized block design with three replications. The highest growth parameters (plant height, number of tillers hill-1, leaf area index and dry matter production), yield parameters (number of panicles m-2, number of filled grains panicles-1 and Test weight) and rice yields (grain and straw yields) were found in both seasons with RDF + GM @ 6.25 t ha-1 + PM @ 2 t ha-1 + Si @ 200 kg ha-1. However, applying RDF + PM @ 2 t ha-1 + Si @ 200 kg ha-1 through DE increased net income and benefit cost ratio in 2022 and 2023. Based on the results of two-year field experiment, it can be concluded that rice productivity and profitability can be improved through the application of RDF + PM @ 2 t ha-1 + Si @ 200 kg ha-1 through DE.